2022
DOI: 10.5713/ab.21.0539
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin seed extract supplementation enhances the growth performance, meat quality, and nutrients digestibility, and reduces gas emission in broilers

Abstract: Objective: A thirty-five-dayfeeding trial was carried out to determine the effect of dietary inclusion of silymarin seed extract on growth performance, nutrient digestibility, excreta microbiota, excreta gas emission, blood profiles, and meat quality in broiler. Methods:A total of 1088 one-day-old Ross 308 broiler chicks (mixed-sex) with an initial body weight of 42.34 ± 0.82g, were randomly allocated into 1 of 4 dietary treatments with 17 replicates of 16 chicks per cage and fed a basal diet supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…As mentioned by Yan, Meng, et al (2012), the incorporation of herbs into a piglet diet enhanced the energy digestibility of nutrients. As mentioned by Shanmugam et al (2022), the incorporation of Silymarin (0%, 0.02%, 0.04% and 0.06%) increased nutrient digestibility of dry matter, nitrogen and energy (Figure 3). PFAs boosted the body's natural and pancreatic relative secretions of proteolytic enzymes, primarily trypsin, protease and bile, and thus contributed to increasing feed conversion efficiency and feed utilization (Gopi et al, 2014).…”
Section: Pfa As Digestibility Enhancermentioning
confidence: 55%
See 2 more Smart Citations
“…As mentioned by Yan, Meng, et al (2012), the incorporation of herbs into a piglet diet enhanced the energy digestibility of nutrients. As mentioned by Shanmugam et al (2022), the incorporation of Silymarin (0%, 0.02%, 0.04% and 0.06%) increased nutrient digestibility of dry matter, nitrogen and energy (Figure 3). PFAs boosted the body's natural and pancreatic relative secretions of proteolytic enzymes, primarily trypsin, protease and bile, and thus contributed to increasing feed conversion efficiency and feed utilization (Gopi et al, 2014).…”
Section: Pfa As Digestibility Enhancermentioning
confidence: 55%
“…PFA, phytogenic feed additives. F I G U R E 3 Effect of PFA (silymarin) on nutrient digestibility (Shanmugam et al, 2022). PFA, phytogenic feed additives.…”
Section: Silymarin As a Pfasmentioning
confidence: 99%
See 1 more Smart Citation
“…Saeed et al (2019) noted that silymarin might protect liver cells through membrane stability, free radical elimination, production of hepatocyte protein and controlling the immunological response. The improved blood profile was confirmed by Shanmugam et al (2022), however, comparison between the absorption rate in blood of different type of silymarin was not done yet. In the livestock industry mostly, powdered form is used.…”
Section: Introductionmentioning
confidence: 97%
“…Silymarin has recently been identified as a strong hepatoprotective additive in poultry feed (Saeed et al, 2019). Improved feed utilisation, feed intake, nutrient digestibility, excreta microbial count was found in broiler supplemented with silymarin (Shanmugam et al, 2022; Tedesco et al, 2004). Previous research has shown that feeding S. marianum herb to rabbits at 5% and 10% increased aroma as well as flavour of meat (Cullere et al, 2016).…”
Section: Introductionmentioning
confidence: 99%